On Positioning of Business, Management and Economics Fields of Study in the University Space - Nairz‑Wirth, Erna; Wurzer , Marcus (Edukacja Ekonomistów i Menedżerów, 2015)
Based on available studies on business and management fields of study as upwardly‑mobile university field of study choices as a basis, this study seeks to test this hypothesis of upward mobility. In doing so, it endeavours to identify correlations between field of study choice and educational background and between field of study choice and gender. The base data is taken from a survey of all domestic first‑time students at Austrian universities in the 2011/12 winter semester (N=27,575). This data was subject to a correspondence analy‑ sis, which allowed us to visualise and interpret the relations between the positions of these fields of study in the university space. The results indicate a clearly structured (stratified) university space. Our supplementary regression analysis shows that the upwardly‑mobile higher education choice hypothesis can be confirmed for the fields of study studied. Our analyses also confirm the feminisation hypothesis for the business and management fields of study studied: women significantly more frequently select fields of study which lead to a career in a pedagogic (business education), social (social economy) or language (international business and management) context. In the group of fields of study explored, business education fields of study had both the highest share of first‑time students and the highest level of feminisation. In contrast, economics fields of study, which were included in the analysis in addition to the business studies and management fields of study, have a sig‑ nificantly higher share of male students and the lowest share of higher education climbers.